Revivalisme Candi Sapto Argo Sido Langgeng Blitar - Poniman (Jurnal Penelitian Agama Hindu, 2022)
Change is a common thing for the continuity of religious life which is adapted to the conditions of ikhsa, village magic, kala, tattwa (Manavadharmasastra VII: 100) that is based on ideas or ideas then abilities accompanied by the area where it occurs and then adapted to the next era that the change does not violate the truth or provisions in the teachings of Hinduism itself. Likewise, what happened to the life system of the Javanese Hindus, in this case, focused on the locus of research that occurred at Sapto Argo Sido Langgeng Temple, that based on initial observations, temple revivalism had occurred. This study aims to find the causes of temple revivalism. Theree are problems that need to be investigated, namely why Javanese Hindus practice temple revivalism. In order to get results on these problems, the researchers used several theories, namely; Life Needs Theory and Functional Structural Theory. This research is a qualitative disain, therefore researchers use qualitative research methods. There is the role of the researcher is needed as the main instrument in this research so that the researcher uses the participatory observation method which is supported by in-depth interviews, online data tracking and documentation. The results of the research include the factors that underlie the emergence of temple Revivalism in the life of Javanese Hindus including the need for holy places, historical influences, customary and cultural influences, the desire to rebuild a temple-style building like in the days of the Hindu kingdoms in the past. Its function is as a means of ritual, a place to deepen religious teachings, maintain identity, preserve customs and culture. the implication is able to strengthen socio-cultural identity, religious passion, religious intelligence.